PERAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR - Ahmad Eskha (UIN Imam Bonjol Padang, 2018)
Abstract: A library is a work unit of an institution that contains a collection of books to support learning resources that are arranged to be read, studied and used as reference material. An educational institution might not be well organized if the teachers and students are not supported by the learning resources needed to organize teaching and learning activities. Smith et al in his encyclopedia book entitled